2013
DOI: 10.1007/s00439-013-1322-3
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial solute carrier SLC25A5 at Xq24 is a novel candidate gene for non-syndromic intellectual disability

Abstract: Loss-of-function mutations in several different neuronal pathways have been related to intellectual disability (ID). Such mutations often are found on the X chromosome in males since they result in functional null alleles. So far, microdeletions at Xq24 reported in males always have been associated with a syndromic form of ID due to the loss of UBE2A. Here, we report on overlapping microdeletions at Xq24 that do not include UBE2A or affect its expression, in patients with non-syndromic ID plus some additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…It has already been shown that MTA‐HDAC containing complexes can deacetylate non‐histone targets like p53 , ATF4 , and HIF1α . Finally we note that genetic studies on patients with intellectual disabilities have identified GATAD2 and SLC25A5 as possible co‐actors in this condition ; the direct interaction between GATAD2 and SLC25A5, as observed in our pull‐down assays, could thus have a role to play in this disease through a yet unknown mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…It has already been shown that MTA‐HDAC containing complexes can deacetylate non‐histone targets like p53 , ATF4 , and HIF1α . Finally we note that genetic studies on patients with intellectual disabilities have identified GATAD2 and SLC25A5 as possible co‐actors in this condition ; the direct interaction between GATAD2 and SLC25A5, as observed in our pull‐down assays, could thus have a role to play in this disease through a yet unknown mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, the GUCY2F [MIM 300041] and SLC25A43 [MIM 300641] truncating variants did not co-segregate with XLID in the family in which they were identified and other rare protein truncating variants were reported in ESP6500 and in other healthy male controls. 81, 82 Furthermore, COL4A6 is part of a contiguous gene deletion causing Alport syndrome [MIM 301050], a childhood onset progressive haematuric glomerulopathy with high-frequency sensorineural hearing loss and typical ocular signs, and for MAP3K15 other stop-gain variants have been identified in male controls. 3 CXorf64 and FATE1 [MIM 300450] truncating variants were identified in the same family and both did not co-segregate with XLID.…”
Section: Resultsmentioning
confidence: 99%
“…Its dysregulation leads to various movement disturbances, dementia and hypogonadotropic hypogonadism [44,45]. Thus, it is not surprising that a growing group of ID proteins are directly involved in UPS-mediated protein degradation, such as UBE3A [46] [47], UBE2A [48,49,50,51], UBE3B [52,47], HUWE1 [53,54,55], MID1 [56][57][58][59], CUL4B [60,[61][62][63], UBR1 [64,65,66], TRIP12 [67][68][69], and RNF216 [45,[70][71][72].…”
Section: Discussionmentioning
confidence: 99%